Efficient Direct Organogenesis from Shoot Tips and Nodal Segments of Ash Gourd (Benincasa Hispida L.) - Kausar, M; Parvin, S; Haque, ME; Khalekuzzaman, M; Sikdar, B; Islam, MA (Journal of Life and Earth Science, 2014)
The effect of external application of phytohormone on explants viz., shoot tips and nodal segments of ash gourd (Benincasa hispida L.) was tested on the frequency of shoot and root induction. Shoot tips and nodal segments were cultured on MS medium supplemented with different concentrations and combinations of cytokinins (BAP, Kinetin), auxin (IBA, NAA) and gibberellic acid (GA3) for multiple shoot formation and root induction. The highest number (up to 90%) of multiple shoot formation was obtained from the shoot tips in MS medium fortified with 1.5 mg/l BAP + 0.2 mg/l GA3, where average number of shoots per culture was 5.55. In case of nodal segment, better response (up to 78%) for shoot multiplication was found in MS with 2.0 mg/l BAP + 0.2 mg/l GA3. The concentration of 1.0 mg/l IBA was found to be most effective for root initiation in microshoot developed from both types of explants. Rooted plantlets were acclimatatized and established in sandy soil with good survival rate DOI: http://dx.doi.org/10.3329/jles.v8i0.20135 J. Life Earth Sci., Vol. 8: 17-20, 2013